Minoxidil in androgenic alopecia: New formulations with Improved delivery - Alaa Al-taie; Myasar Al-kotaji; Hani Almukhtar (University of Mosul, 2022)
Background: Minoxidil was introduced into the market as a hypotensive agent, however, aftermarketing, the hypertrichosis side effect was reported by almost all users. This adverse effect encourages the repositioning or repurposing the use of minoxidil as a topical preparation for the treatment of hair loss. Objective: topical minoxidil is contemplated as an effective treatment to reduce hair loss and promote regrowth in conditions like androgenetic alopecia. However, the unerring mode of action of minoxidil remains obscure. In this review, the molecular pharmacology of minoxidil, the response of hair follicles to treatment, and the side effects of the topically applied minoxidil were reviewed. The innovation in the formulation of topical preparation toward enhancing delivery was highlighted focusing on the use of nanoemulsion and nanocarrier systems such as nanoparticles and liposomes that enriched the topical delivery.